2014
DOI: 10.1111/j.2040-0209.2014.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with Health Markets in Low and Middle‐Income Countries

Abstract: SummaryMany low and middle-income countries have pluralistic health systems with a variety of providers of health-related goods and services in terms of their level of training, their ownership (public or private) and their relationship with the regulatory system. The development of institutional arrangements to influence their performance has lagged behind the spread of these markets. This paper presents a framework for analysing a pluralistic health system. The relationships between private providers of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…We adapted the theoretical framework ( figure 1 ) for health market systems proposed by Bloom et al 43 to take into account key stakeholders in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…We adapted the theoretical framework ( figure 1 ) for health market systems proposed by Bloom et al 43 to take into account key stakeholders in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…This happened mainly due to financial issues, as seeking care in the hospital or with a specialist doctor can entail expensive spending for diagnostic tests and consultation fees. Previous study has pointed out the preference of poor populations to seek care in informal providers, amongst others because of affordability issue [34]. However, the current study found that providers also failed to give appropriate treatment because they did not have the right diagnostic tool or medicine.…”
Section: Discussionmentioning
confidence: 59%
“…In 2012, we undertook work for the Rockefeller Foundation that sought to inform their future investments in health markets. Whereas health markets are sometimes viewed solely through the lens of private health care providers, our approach was broader, viewing such providers as one of many inter-connected actors who work within a market system [ 1 ]. We were interested in better understanding the interactions between these many actors, including public and private health care providers, payors, regulators, and civil society organizations, and the rules and regulations that govern the market.…”
mentioning
confidence: 99%